Rendimiento ofensivo en situaciones de desigualdad numérica durante las exclusiones en balonmano femenino - Martin-Gonzalez, N.; Martinez-Merino, N.; Usabiaga-Arruabarrena, O.; Martos-Garcia, D. (Revista Internacional de Ciencias del Deporte, 2020)
The aims of this study were: i) to describe the situations of numerical inequality due to exclusions during the Female Handball at Panamerican Games Tournament 2015; ii) to analyse the efficacy to relate these situations with the final performance and results. All matches played by teams ranked 1 to 4 in the tournament were analysed using the observational methodology. An ad hoc tool was created in order to develop the observation. A total of 14 matches were analysed in which 461 situations of numerical inequality occurred. Differences among different categories were analysed using chi-square test. Statistical significance was considered when p < 0.05. The main number of actions was concentrated during the second part of the matches (p < 0.05). Results showed the winners being more efficient than losers in the majority of the variables studied (p < 0.05). Winner teams scored a higher percentage of goals and showed a lower percentage of throws out than loser teams. Winner teams showed a more efficient performance in their attack efficacy (number of goals scored in relation to the number of attacks) while playing in inferiority. It was concluded that winner teams convert more goals than loser teams and they are more efficient during actions under numerical inequality.